Standup time estimation of undercut moist sand slope using numerical simulation - Dul, Laddawon; Leelasukseree , Cheowchan (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 25, 2020)
Undercut slope is defined as a slope, which is excavated at its toe. An undercut slope would be failed if undercut width is equal to or greater than its maximum undercut width. Sometimes, the undercut slope is temporarily stable. The undercut slope could displace slowly over a period and it finally fails. The period of undercut slope in stable is called standup time. In this paper, the standup time was estimated by using numerical simulations. A series of numerical simulations using 3DEC was performed to study of standup time of undercut slopes. The numerical models were applied the physical properties and creep parameters of moist sand, which were tested in laboratory. Mohr-Coulomb and Burgers model were assigned to the numerical simulations. The slope inclination of the numerical models was varied. The slope inclinations were 50ᵒ, 30ᵒ, 18ᵒand 15ᵒ. The undercut slope models showed a relationship between slope inclination, undercut width and standup time. When the slope inclination was shallower than the friction angle of bedding plane, its standup time and undercut width were longer and wider than the steeper. The slope inclination was inversely proportional to undercut width while the undercut width was proportion to the standup time.